Treatment strategy of adding transcatheter arterial chemoembolization to sorafenib for advanced stage hepatocellular carcinoma. Issue 1 (13th October 2020) - Lee, Wei‐Chen; Hung, Hao‐Chien; Lee, Jin‐Chiao; Wang, Yu‐Chao; Cheng, Chih‐Hsien; Wu, Tsung‐Han; Lee, Chen‐Fang; Wu, Ting‐Jung; Chou, Hong‐Shiue; Chan, Kun‐Ming
Abstract: Background: Therapeutic effect and immunosuppressor cell alteration in adding transcatheter arterial chemoembolization (TACE) to sorafenib for advanced stage hepatocellular carcinoma (HCC) remain unclear. Aims: To examine the therapeutic effect and immunosuppressor cell alteration in adding TACE to sorafenib. Methods: Forty‐four advanced stage HCC patients were divided into group A (n = 17) treated by sorafenib (400‐600 mg/day) alone and group B patients (n = 27) treated by sorafenib and TACE. The frequency of regulatory T‐cells and myeloid‐derived suppressor cells (MDSC), and patients' outcomes were examined. Advanced HCC patients' survival was improved by adding TACE to sorafenib if N/L was reduced from ≥2.5 to <2.5 by TACE. Results: The median (interquartile) follow‐up for all patients was 8.5 (3.5 to 15.5) with a range from 1 to 71 months. The median (interquartile) survival was 5.0 (2.3‐11.3) months for group A and 11.0 (5.0‐19.0) months for group B patients ( P = .024). In group A, the patients (n = 8) with neutrophil‐to‐lymphocytes ratio (N/L) < 2.5 had better survival than the patients (n = 9) with N/L ≥ 2.5 ( P = .006). In group B, 6 of 13 patients with N/L ≥ 2.5 had N/L reduction to <2.5 after combination therapy of sorafenib and TACE, and their 6‐month, 1‐year and 2‐year survival were improved ( P = .013). For immune cell examination, the frequency of CD4 + and CD8 + T‐lymphocytes, regulatory T‐cell and MDSC were not altered by sorafenib treatment. However, actual number of lymphocytes had a tendency to increase (from 978.5 ± 319.4/mm 3 prior to treatment to 1378.0 ± 403.3/mm 3, P = .086) for the patients with N/L reduction. Conclusion: Immunosuppressor cells were not altered by sorafeinb. Patients' survival was improved if N/L ≥ 2.5 was reduced to <2.5 by TACE.